2003
DOI: 10.1111/j.0013-9580.2003.06203.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent Induction of Cytochrome P450 (CYP) 3A4 and Activation of Pregnane X Receptor by Topiramate

Abstract: Summary: Purpose:In clinical studies, topiramate (TPM) was shown to cause a dose-dependent increase in the clearance of ethinyl estradiol. We hypothesized that this interaction results from induction of hepatic cytochrome P450 (CYP) 3A4 by TPM. Accordingly, we investigated whether TPM induces CYP3A4 in primary human hepatocytes and activates the human pregnane X receptor (hPXR), a nuclear receptor that serves as a regulator of CYP3A4 transcription.Methods: Human hepatocytes were treated for 72 h with TPM (10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 24 publications
(50 reference statements)
1
34
1
Order By: Relevance
“…The isoforms of UGT involved in MHD glucuronidation have not yet been identified [24] , thus this hypothesis requires further validation. Some studies [14,25] showed a modest inducing effect of higher doses (up to 200 mg/d) of TPM on CYP3A4 and possible effects on the activity of UGTs. Thus, the CYP and UGT-mediated metabolism of MHD might also be induced by a high dose of TPM.…”
Section: Discussionmentioning
confidence: 99%
“…The isoforms of UGT involved in MHD glucuronidation have not yet been identified [24] , thus this hypothesis requires further validation. Some studies [14,25] showed a modest inducing effect of higher doses (up to 200 mg/d) of TPM on CYP3A4 and possible effects on the activity of UGTs. Thus, the CYP and UGT-mediated metabolism of MHD might also be induced by a high dose of TPM.…”
Section: Discussionmentioning
confidence: 99%
“…The time-and dose-dependent induction of CYP3A4 by rifampicin has also been demonstrated in primary cultures of human hepatocytes (11,13,160,161). In human hepatocytes treated with rifampicin, the induction of CYP3A4 activity (measured by testosterone 6b-hydroxylation) was concentration dependent, and the EC 50 for rifampicin was estimated to be 0.3Y0.5 mM (162).…”
Section: Time-and Dose-dependent Cyp Inductionmentioning
confidence: 95%
“…The metabolism of carbamazepine is decreased by the co-administration of valproic acid, leading to an increased risk of carbamazepine toxicity [26,39,40]. On the other hand, oxcarbazepine and topiramate (second generation AEDs) are considered weak CYP2C19 and CYP3A4/5 substrates [46] while lamotrigine and levetiracetam are not CYP substrates [37,47]. Levetiracetam lacks of liver Phase I P450 metabolism and does not induce P450 enzymes in vitro [37,47].…”
Section: Brain Peripheral P450 and Drug Metabolism: Focus On Aedsmentioning
confidence: 99%